Azo dyes with ESIPT core for textile applications and DFT study. (November 2019) - Ramugade, Supriya H.; Warde, Umesh S.; Sekar, Nagaiyan
Abstract: Five azo dyes with ESIPT unit were used to study their application properties. These dyes were used for coloration on polyester (PET), acrylic (AC) and nylon (NY) fabrics. The various properties of fastness, UV blocking, UV protection properties were investigated. Elecrophilicity index was calculated for comparing with the trends in lightfastness properties on PET, NY and AC fabrics. The azo disperse dyes containing electron withdrawing group in3d and3e showed the highest electrophilicity index (7–7.05) and lightfastness (6–7 and 7). The electrochemical characteristics of these dyes were calculated using cyclic voltammetry (CV) and density functional theory. Oscillator strength, vertical excitation, orbital contribution, HOMO-LUMO, and MEP were calculated from experimental and theoretical results (time-dependent density functional theory). Dye3a shows the highest band gap (2.88 eV) and dyes3b, 3c, 3d, 3e showed the lowest band gap (2.60 eV, 2.66eV, 2.72eV, 2.72eV) respectively. Highlights: Dyes3a-3e were successfully applied on polyester, nylon, acrylic fibres. Lightfastness properties correlated well with electrophilicity index. Dye3a shows the highest band gap (2.88 eV). Electrochemical properties were calculated by cyclic voltammetry.